Visualization Analysis of AI-Enabled Ideological and Political Education in Higher Education Based on CiteSpace - Zhang, Qi; Gong, Yue; Wang, Lei (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2025)
This study adopts CiteSpace software to conduct a visualization analysis of artificial intelligence-enabled (AI-enabled) ideological and political educational literature obtained from the China National Knowledge Infrastructure (CNKI) database from 2018 to 2024. The results showed that the number of journal articles regarding AI-enabled ideological and political education exhibits a consistent upward trend. The main authors have not yet formed a scale effect and the degree of collaboration among them was limited. In addition, the research hotspots primarily focused on artificial intelligence-related technologies to improve ideological and political education scenarios and the reform paths of high-educational courses. The findings of this study suggest that future research should consider incorporating interdisciplinary collaboration, technological integration and innovation, and the construction of the curriculum system that contributes to AI-enabled ideological and political education.